Psychosocial Stress with Vaginal Discharge Of Adolescent Women In The New Normal Era - Istiana Asrari Bansu; Nurdiana Lante (Science Midwifery, 2022)
Psychosocial stress experienced by adolescent girls is generally triggered by environmental conditions. Symptoms of stress can be a problem that has an impact on reproductive health such as vaginal discharge. The purpose of this study was to determine the relationship with the incidence of psychosocial stress whitish young women in the Era of the New Normal. This type of research is correlational. Sampling with non-probability sampling. The data collection tool is a questionnaire stress of the Depression Anxiety Stress Scale (DASS 42) and questionnaires incidence of vaginal discharge. Data analysis using Chi-Square test. The results showed that adolescent girls experienced severe stress as many as 52 respondents (56.5%), experienced mild stress 11 respondents (12.0%), adolescents with normal psychosocial stress levels were 29 (31.5%). The adolescents who experienced physiological or normal vaginal discharge were 65 (70.7%) while those who experienced pathological/abnormal vaginal discharge were 27 (29.3%). The results of the statistical test obtained p-value < (0.0 16 < 0.05). Conclusion: there is a significant relationship between psychosocial stress and female adolescent vaginal discharge in Bastiong Karance Village, with a fairly strong correlation strength. So the researchers recommend the importance of psychological counseling and adolescent reproductive health in the new normal era